PENGARUH AROMATERAPI PEPPERMINT TERHADAP PENURUNAN MUAL MUNTAH PADA IBU HAMIL TRIMESTER 1 DI PUSKESMAS PAUH KAMBAR - PRASETYANINGSIH, PRASETYANINGSIH; SYAHRUL, SYAHRUL; RISHEL, RIKA ASTRIA; ARMALINI, RIKA; AMELIA, JIHAN (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2024)
The World Health Organization reported that the incidence of nausea and vomiting in women reached 12.5% ​​in the world with 0.3% in Sweden, 0.5% in California, 0.8% in Canada, 10.8% in China, 0.9% in Norway, 2.2% in Pakistan, 1.9% in Turkey, and in Indonesia reaching 50%-80%. Peppermint aromatherapy containing menthol (35-45%) and menthone (10%-30%) is useful as an antiemetic and antispasmodic on the lining of the stomach and intestines by inhibiting muscle contractions. The ability of peppermint leaves to reduce nausea and vomiting in pregnancy is thought to be related to the content of essential oils such as α-, β-pinenelimonene 1,8- cineole. This study aims to determine the effect of peppermint aromatherapy on reducing nausea and vomiting in pregnant women in the first trimester at the Pauh Kambar Health Center. This research method uses a quasi-experimental design with a one group pretest-posttest design. The population of this study was 70 pregnant women in the first trimester. The number of samples taken was 15 people using purposive sampling technique. Data processing was done using Univariate and Bivariate using t-dependent analysis. The results of the study with the T test showed that there was an effect of peppermint aromatherapy on reducing nausea and vomiting in pregnant women in the first trimester at the Pauh Kambar Health Center (p-value = 0.000 <a = 0.05). It can be concluded that there is an effect of Peppermint Aromatherapy on Reducing Nausea and Vomiting in Pregnant Women in the First Trimester at the Pauh Kambar Health Center.